Thermosensitive Pluronic® hydrogel: prolonged injectable formulation for drug abuse - Katayoun Derakhshandeh; Mahtab Fashi; Seyedalireza Seifoleslami (Dove Medical Press, 2010)
Katayoun Derakhshandeh1, Mahtab Fashi1, Seyedalireza Seifoleslami21Department of Pharmaceutics, Faculty of Pharmacy, University of Medical Science, Kermanshah; 2Research and Development Department, Forensic Medicine Organization, Kermanshah, IranObjective: The main objective of this study was to investigate thermosensitive Pluronic® F-127 (PF-127) hydrogel for the modified release of a potent alcohol and opioid antagonist, naltrexone (NTX) hydrochloride, in a subcutaneous injectable dosage form.Methods: The NTX hydrogels were prepared by the cold method, and the in vitro release profiles of various formulations were evaluated at 37°C using the Franz diffusion cell system. We examined the different PF-127 concentrations, pH of solution, and inorganic salts on drug release from these gels.Results: The data showed an increase in PF-127 content from 20% to 35%, resulting in a decrease in the rate of NTX release. Among the formulations prepared in different pH solutions, pH 7.4 produced the slowest drug release rate. The addition of inorganic salts had no significant effect on drug release. However, these factors appeared to have limited effects on drug release rate. Therefore, to achieve a sustained-release formulation, a NTX and triacetyl β-cyclodextrin (TAβCD) complex was evaluated. The binary systems of NTX/TAβCD in different molar ratios were prepared by the kneading method, and complex formation was demonstrated by differential scanning calorimetry.Conclusion: The results of the current in vitro study indicate that PF-127 gel formulations containing drug complexes with hydrophobic cyclodextrin could be useful for the preparation of a controlled delivery system of water-soluble drugs such as NTX, for a period of more than 140 hours.Keywords: naltrexone, thermosensitive hydrogel, prolonged release, triacetyl β-cyclodextrin, kneading method